Enhancing Entrepreneurial Literacy of PKK Women through Agropreneurship-Based Training in Bulujaya, Jeneponto - Burhanuddin, Burhanuddin; Mustari, Nuryanti; Nadir, Nadir; M., Sudirman; Nur, Indri Apriani; Chandra, Diky; Herman, Herman (Journal of Universal Community Empowerment Provision, 2025)
This study aims to improve agropreneurship-based entrepreneurial literacy for Family Welfare Empowerment (PKK) women in Bulujaya Village, Jeneponto Regency through training in processing corn into value-added products. The background of the study is based on the low entrepreneurial literacy of rural women, especially in aspects of business management, marketing, and the use of digital technology. This study used the Participatory Action Research (PAR) method with a qualitative descriptive approach. The research subjects were PKK women who were active in organizational activities, had an interest in entrepreneurship, and were willing to participate in the training program. Data were collected through observation, in- depth interviews, FGDs, and documentation. The results showed a significant increase in the participants' entrepreneurial literacy after the training, as evidenced by a comparison of pre- test and post-test results. Participants were able to understand the concept of entrepreneurship more professionally, including in managerial, financial, and marketing aspects. In terms of technical skills, participants successfully processed corn into popcorn with various flavors and attractive packaging, thereby increasing the added value of local products. In addition, there was an increase in digital literacy, where PKK women began to utilize social media as a means of product promotion. This training also has social and economic impacts, including increased self-confidence, group solidarity, and the emergence of additional family income, even on a small scale. Thus, agropreneur-based entrepreneurial literacy training has proven effective in empowering women, strengthening family economic resilience, and encouraging the development of local potential in a sustainable manner.